2020
DOI: 10.3390/ijerph17165936
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measures to Assess Active Commuting Physical Activity to School in Young People: A Systematic Review Protocol and Practical Considerations

Abstract: There are no systematic reviews that have identified the existing studies assessing active commuting physical activity (PA) to and from (to/from) school using objective measures, as well as the contribution of both walking and cycling to/from school to PA levels. To fill this gap in the literature, this systematic review will aim (a) to identify existing studies that assess active commuting PA to/from school with objective measures in young people and to examine the contribution of walking and cycling to/from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The present study also shows several strengths: (1) last PRISMA guidelines were followed to ensure that the systematic review was conducted with adequate rigor. In addition, it was registered in PROSPERO and the systematic review protocol was also published 24 ; (2) the quality and risk of bias of the included studies were assessed, as they are different concepts, following the recommendations of Gunnell et al 23 Most studies had a low risk of bias (see Figures S3 and S4 in Additional File 3) and medium quality (see Tables S3 and S4 in Additional File 3); (3) a meta‐analysis was conducted to contribute to the scientific literature on how much device‐measured LPA and MVPA is related to ACS; (4) to best of our knowledge, it is the first systematic review and meta‐analysis that separates the home‐school and school‐home trips, suggesting that they should be evaluated separately.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study also shows several strengths: (1) last PRISMA guidelines were followed to ensure that the systematic review was conducted with adequate rigor. In addition, it was registered in PROSPERO and the systematic review protocol was also published 24 ; (2) the quality and risk of bias of the included studies were assessed, as they are different concepts, following the recommendations of Gunnell et al 23 Most studies had a low risk of bias (see Figures S3 and S4 in Additional File 3) and medium quality (see Tables S3 and S4 in Additional File 3); (3) a meta‐analysis was conducted to contribute to the scientific literature on how much device‐measured LPA and MVPA is related to ACS; (4) to best of our knowledge, it is the first systematic review and meta‐analysis that separates the home‐school and school‐home trips, suggesting that they should be evaluated separately.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta‐analysis was registered in the PROSPERO International Prospective Register of Systematic review (Registration number: CRD42020162004). In addition, for more information about the methodological process of this systematic review, further details can be found in the protocol 24 . The current study was conducting according to the checklist “Preferred Reporting Items for Systematic Reviews and Meta‐analysis: The PRISMA Statement” 22 (see Tables S1 and S2 in Additional File 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations